Compliance with the Community Pharmacy Project after Accreditation by the Pharmacy Council (Thai) - Boonchoong, Nonglek; Chanakij, Theeraporn; Dorkrakklang, Phakornkij; Wongsa, Phumiwasit; Sootsol, Sakkosin; Yospanya, Supaksana (Asia-Pacific Journal of Science and Technology, 2017)
This survey research aimed to study action towards the standard criteria of the qualified pharmacy community after accreditation by the Pharmacy Council. The data was collected by posting self-administered questionnaires to pharmacists working in 10) accredited drugstores during Oct.-Dec., 2005. The results show that they were able to comply with 5 sections of those criteria in order: I) services and social participation 2) site, equipment and facilities 3) pharmaceutical care service 4) law and jurisprudence, and 5) the quality control process. The mean scores were 4.51, 4.32, 4.15, 4.08 and 3.93 respectively (full score = 5). Moreover, the opinion level on the outcome of this project and the appropriateness of those criteria were high with mean scores of 4.07 and 3.62 respectively. The satisfaction in qualified community pharmacies was also determined in 255 customers by accidental sampling. They were satisfied with pharmaceutical care services followed by site and products with mean scores of 4.13, 4.2 and 3.94 respectively,